Multidimensional analysis of 5G antenna with coaxial cables and circular slots using computational resources and polynomial analysis - Filipe C. de Andrade; Giselle Francine B. Muniz; Ana Karine D. C. Brandão; Kenedy Marconi G. dos Santos; Polyane A. Santos; Tagleorge M. Silveira (Journal of Microwaves, Optoelectronics and Electromagnetic Applications, 2024)
Abstract The study proposes a multidimensional mathematical modeling of antennas using coaxial cables for 5G, with emphasis on the relationship between cable length, frequency, and VSWR. By employing a final configuration incorporating five circular slots of 6 mm and operating at a frequency of 3.5 GHz, a linear pattern in this relationship was identified. Despite the recognized challenges in accurately modeling VSWR concerning cable length, the study enabled antenna optimization through the determination of the proposed antenna’s properties and their respective mathematical correlations.